2019
DOI: 10.1017/s1368980019001812
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-sweetened beverage consumption among Indigenous Australian children aged 0–3 years and association with sociodemographic, life circumstances and health factors

Abstract: Objective:To explore beverage intake and associations between sugar-sweetened beverage (SSB) intake and sociodemographic, life circumstances, health and well-being factors in a national cohort of Indigenous children.Design:We calculated prevalence ratios for any SSB consumption across exposures, using multilevel Poisson regression (robust variance), adjusted for age group and remoteness. A key informant focus group contextualised these exploratory findings.Setting:Diverse settings across Australia.Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…Indigenous people in Australia have experienced unfair treatment, such as colonisation, racism, and cultural genocide, which has profoundly impacted their physical, mental and emotional health. 26 These political and historical factors, have exacerbated the more commonly investigated influences on dental caries, such as: increased consumption of sugarsweetened beverages 27 ; lack knowledge and awareness of oral health; poor oral health behaviours and access to care. 28 In recent years, the government and states have taken various measures to narrow the gap between Indigenous and non-Indigenous children with dental caries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indigenous people in Australia have experienced unfair treatment, such as colonisation, racism, and cultural genocide, which has profoundly impacted their physical, mental and emotional health. 26 These political and historical factors, have exacerbated the more commonly investigated influences on dental caries, such as: increased consumption of sugarsweetened beverages 27 ; lack knowledge and awareness of oral health; poor oral health behaviours and access to care. 28 In recent years, the government and states have taken various measures to narrow the gap between Indigenous and non-Indigenous children with dental caries.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a trial in remote Indigenous communities of Australia's Northern Territory once again confirmed that fluoride varnish could effectively prevent dental caries in children. 27,32 So while, programs exist to prioritise and provide timely care for Indigenous children, it appears that on a broader level they are not having much of an impact and this could be due to the limited reach as well as the lack of continuity of programs.…”
Section: Discussionmentioning
confidence: 99%
“…Diet and lifestyle modification such as increased consumption of fruits/vegetables and reduced consumption of processed foods is routinely recommended to reduce the risk of gastric cancer [11], but many Indigenous people face barriers to these behavioral changes. Research from Australia shows that Indigenous populations consume a greater proportion of sugar-sweetened food and beverages compared to other populations in Australia [18]. A primary driver is the high price and decreased access to healthier food options and safe drinking water [18].…”
Section: Choicesmentioning
confidence: 99%
“…Research from Australia shows that Indigenous populations consume a greater proportion of sugar-sweetened food and beverages compared to other populations in Australia [18]. A primary driver is the high price and decreased access to healthier food options and safe drinking water [18]. In Canada, a review of obesity among First Nations communities observed that fluctuating food prices by season, lack of access to healthy food options, and ease of access to convenience stores are factors in the increased levels of obesity [12,19].…”
Section: Choicesmentioning
confidence: 99%
“…The ADWG Good definition reflects the ADWG definition of 'good' water quality and the emphasis in the guidelines on water suppliers meeting consumer expectations. In practice, accounting for aesthetic considerations in defining basic service levels is necessary because: (i) unpalatable water affects consumer risk perceptions, potentially leading to indirect health impacts from accessing unsafe alternative sources of hydration 48,64,65 , including sugary drinks 66,67 ; (ii) buying bottled or trucked water due to distrust of water services 68,69 is a financial burden for low-income households inconsistent with affordable access; and (iii) high levels of hardness and TDS may affect water infrastructure integrity, operational costs, and safety 70 . Note that the ADWG definition of 'good' water also includes 'taste and odour' which is specified as "not offensive to most people" 21 .…”
Section: Definitions Of a Basic Level Of Drinking Water Qualitymentioning
confidence: 99%